The Transcription Factor Aabzip9 Positively Regulates the Biosynthesis of Artemisinin in Artemisia annua - Shen, Qian; Huang, Huayi; Zhao, Yu; Xie, Lihui; He, Qian; Zhong, Yijun; Wang, Yuting; Wang, Yuliang; Tang, Kexuan (Frontiers in Plant Science, 2019)
Artemisinin-based therapies are the only effective treatment for malaria, which reached to 219 million cases and killed 435,000 people in 2017. To meet the growing demand for artemisinin and make it accessible to the poorest, genetic engineering of Artemisia annua becomes one of the most promising approaches to improve artemisinin yield. In this work, AabZIP9 transcription factor has been identified and characterized. The expression profile of AabZIP9 revealed that it was clustered with the artemisinin specific biosynthetic pathway genes ADS, CYP71AV1, DBR2, and ALDH1. Furthermore, the transiently dual-LUC analysis showed that the activation of ADS promoter was enhanced by AabZIP9. Meanwhile, yeast one-hybrid assay showed that AabZIP9 was able to bind to the “ACGT” cis-element present in both ADS and CYP71AV1 promoters. AabZIP9 gene was driven by the constitutive CaMV35S promoter and the glandular trichome specific CYP71AV1 promoter and stably transformed into A. annua plants. The transcript level of AabZIP9 was increased in both of the 35S and CYP71AV1 driven transgenic plants compared with the wild type or GUS control plants. All the transgenic A. annua plants overexpressing AabZIP9 showed elevated transcript level of ADS, but the transcription levels of CYP71AV1, DBR2 and ALDH1 have no significant change in both types of transgenic plants. The significantly up-regulated ADS promoted the accumulation of artemisinin, dihydroartemisinic acid and artemisinic acid biosynthesis in the transgenic A. annua plants. These results suggest that AabZIP9 can positively regulate the biosynthesis of artemisinin.